Enantioselective crossed intramolecular [2+2] photocycloaddition reactions mediated by a chiral chelating Lewis acid. Issue 8 (8th February 2022) - Rigotti, Thomas; Schwinger, Daniel P.; Graßl, Raphaela; Jandl, Christian; Bach, Thorsten
Abstract : An enantioselective crossed [2+2] photocycloaddition is presented which proceeds under visible light irradiation in the presence of a chiral Lewis acidic metal complex. Chelation of two oxygen atoms to the metal centre accounts for the observed enantioface differentiation. Abstract : In intramolecular [2+2] photocycloaddition reactions, the two tethered olefins can approach each other in a straight or in a crossed fashion. Despite the fact that the latter reaction mode leads to intriguing, otherwise inaccessible bridged skeletons, there has so far not been any enantioselective variants thereof. This study concerned the crossed [2+2]-photocycloaddition of 2-(alkenyloxy)cyclohex-2-enones to bridged cyclobutanes. It was found that the reaction could be performed with high enantioselectivity (80–94% ee) under visible light conditions when employing a chiral rhodium Lewis acid as a catalyst (2 mol%).